The thesan project: Lyman-α emission and transmission during the Epoch of Reionization. Issue 3 (24th March 2022) - Smith, A; Kannan, R; Garaldi, E; Vogelsberger, M; Pakmor, R; Springel, V; Hernquist, L
ABSTRACT: The visibility of high-redshift Lyman-alpha emitting galaxies (LAEs) provides important constraints on galaxy formation processes and the Epoch of Reionization (EoR). However, predicting realistic and representative statistics for comparison with observations represents a significant challenge in the context of large-volume cosmological simulations. The thesan project offers a unique framework for addressing such limitations by combining state-of-the-art galaxy formation (IllustrisTNG) and dust models with the arepo-rt radiation-magnetohydrodynamics solver. In this initial study, we present Lyman-alpha centric analysis for the flagship simulation that resolves atomic cooling haloes throughout a (95.5 cMpc)^3 region of the Universe. To avoid numerical artefacts, we devise a novel method for accurate frequency-dependent line radiative transfer in the presence of continuous Hubble flow, transferable to broader astrophysical applications as well. Our scalable approach highlights the utility of LAEs and red damping-wing transmission as probes of reionization, which reveal nontrivial trends across different galaxies, sightlines, and frequency bands that can be modelled in the framework of covering fractions. In fact, after accounting for environmental factors influencing large-scale ionized bubble formation such as redshift and UV magnitude, the variation across galaxies and sightlines mainly depends on random processes including peculiar velocities and self-shielded systems that strongly impact unfortunate rays more than others. Throughout the EoR local and cosmological optical depths are often greater than or less than unity such that the exp (− τ) behaviour leads to anisotropic and bimodal transmissivity. Future surveys will benefit by targeting both rare bright objects and Goldilocks zone LAEs to infer the presence of these (un)predictable (dis)advantages.